The Influence of Service Quality, Brand Image, and Customer Trust on Customer Loyalty among Tenth-Grade Students at a Learning Center - Linda Wahyuningsih; Ni Luh Wayan Sayang Telagawathi; Ni Made Ary Widiastini (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the influence of service quality, brand image, and customer trust on customer loyalty among Grade X students at the Ruangguru Denpasar Melati Tutoring Institution. The research is motivated by the growing importance of customer loyalty in maintaining the competitiveness and long-term sustainability of tutoring institutions within an increasingly competitive educational services industry. A quantitative approach with a causal research design was employed. The study involved 30 respondents selected using a saturated sampling technique. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics. The findings reveal that service quality, brand image, and customer trust each have a positive and statistically significant effect on customer loyalty. Furthermore, the three independent variables simultaneously exert a significant influence on customer loyalty, indicating that they collectively play an essential role in strengthening students' loyalty toward the institution. Among these factors, continuous improvements in service quality, the development of a strong and favorable brand image, and the enhancement of customer trust are crucial for fostering long-term customer relationships. The findings provide valuable managerial implications for the Ruangguru Denpasar Melati Tutoring Institution in formulating effective strategies to improve customer satisfaction, strengthen competitive advantage, and sustain customer loyalty in the educational services market.